Finding a balance between remote and office work : A qualitative study on the experiences of knowledge workers on hybrid work arrangements - Darlington, Julia (My University, 2024)
The use of flexible work arrangements, such as remote and hybrid work, has been gaining popularity globally over the past few decades. Although remote work adoption was already on the rise before the COVID-19 pandemic, the pandemic significantly accelerated this trend. A new trend that has gained considerable popularity post-pandemic is the hybrid working model, which combines both remote and office work. This study examines how employees experience hybrid work, discussing the benefits and drawbacks based on their experiences. The data for the study was gathered through 17 qualitative interviews with knowledge workers employed in an organization operating in the financial sector in Finland. By examining various aspects of both remote and office work, such as work-life balance, productivity and community building, this study provides understanding on factors that should be considered when discussing hybrid work arrangements. Based on the findings, this study supports the use of hybrid work arrangements, arguing that they provide the most balanced approach to organizing work post-pandemic. Furthermore, the interviews suggested that hybrid work effectively mitigates the potential drawbacks of excessive remote or office work, allowing employees to benefit from both work modes. Additionally, this study contributes to existing literature, which has often explored remote and flexible work arrangements through theories that utilize the reciprocal nature of the employment relationship, such as psychological contract theory. This study underscores the pandemic's impact on the psychological contract between employees and employers by indicating the importance of maintaining flexible work arrangements to uphold the psychological contract. It reveals a shift towards valuing flexibility post-pandemic, suggesting that rigid work arrangements may lead to job dissatisfaction and potentially end the employment relationship. The research contrasts with previous studies by highlighting that the lack of flexibility could drive employees to seek new job opportunities altogether. It supports the idea of a balanced approach to remote and office work as the most favourable, emphasizing the necessity for organizations to adapt to changing expectations around work flexibility.

Joustavat työjärjestelyt, kuten etä- ja hybridityö, ovat kasvattaneet suosiotaan maailmanlaajuisesti viime vuosikymmeninä. Vaikka etätyön käyttö oli lisääntymässä jo ennen COVID-19-pandemiaa, pandemia kiihdytti tätä suuntausta merkittävästi. Uusi suuntaus, joka on saavuttanut huomattavan suosion pandemian jälkeen, on hybridityömalli, jossa yhdistyvät sekä etä- että toimistotyö. Tässä tutkimuksessa tarkastellaan, miten työntekijät kokevat hybridityön, ja keskustellaan heidän kokemustensa perusteella hyödyistä ja haitoista. Tutkimuksen aineisto kerättiin 17 laadullisella haastattelulla, jotka tehtiin Suomessa rahoitusalalla toimivassa organisaatiossa työskentelevien tietotyöntekijöiden kanssa. Tutkimuksessa analysoidaan sekä etä- että toimistotyöhön liittyviä eri näkökohtia, kuten työn ja yksityiselämän tasapainoa, tuottavuutta ja yhteisöllisyyden rakentamista, ja sen tavoitteena on antaa kattava käsitys tekijöistä, jotka olisi otettava huomioon, kun keskustellaan hybridityöjärjestelyistä. Tulosten perusteella tässä tutkimuksessa tuetaan hybridityöjärjestelyjen käyttöä ja väitetään, että ne tarjoavat tasapainoisimman lähestymistavan työn organisointiin pandemian jälkeen. Lisäksi haastattelujen perusteella hybridityöskentelyn koettiin lieventävän tehokkaasti liiallisen etätyön tai toimistotyön mahdollisia haittoja, jolloin työntekijät voivat hyötyä molemmista työmuodoista. Lisäksi tämä tutkimus täydentää olemassa olevaa kirjallisuutta, jossa etätyöjärjestelyjä ja joustavia työjärjestelyjä on usein tutkittu työsuhteen vastavuoroisuutta hyödyntävien teorioiden, kuten psykologisen sopimusteorian, avulla. Tässä tutkimuksessa korostetaan pandemian vaikutusta työntekijöiden ja työnantajien väliseen psykologiseen sopimukseen osoittamalla, että joustavien työjärjestelyjen säilyttäminen on tärkeää psykologisen sopimuksen ylläpitämiseksi. Tutkimuksessa saadun datan perusteella voidaan todeta, että pandemian jälkeen on siirrytty arvostamaan joustavuutta, mikä viittaa siihen, että jäykät työjärjestelyt voivat johtaa työtyytymättömyyteen ja mahdollisesti työsuhteen päättymiseen. Tutkimus on ristiriidassa aiempien tutkimusten kanssa, sillä siinä korostetaan, että joustavuuden puute voi saada työntekijät etsimään kokonaan uusia työmahdollisuuksia. Tutkimuksessa tuetaan ajatusta tasapainoisesta lähestymistavasta etätyöhön ja toimistotyöhön, mikä oli kerätyn aineiston perusteella kaikkein suotuisinta, ja korostetaan, että organisaatioiden on sopeuduttava työn joustavuuteen liittyviin muuttuviin odotuksiin.
Keywords: hybrid work, remote work, flexible work arrangements, office work, psychological contract